A realidade do sono dos cuidadores familiares de pessoas idosas com Parkinson e/ou Alzheimer - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Introduction: In Brazil, the number of elderly people is increasing every year at an accelerated rate. Together with this, neurodegenerative diseases, such as Alzheimer's and Parkinson's, are affecting the elderly population more frequently, and consequently, increasing the number of dependent elderly people. Currently, most of those who are dependent on help to perform basic activities of daily living are cared for by their families. Thus, the lack of support to this family caregiver and his/her inexperience contribute to overload and stress situations, directly influencing the caregiver's life and the care provided to the elderly person. Furthermore, an insufficient daily amount of sleep is considered a public health concern, noting the need to investigate the quality of sleep and what are the factors of interference in the lives of family caregivers. In this sense, it is known that sleep cycle disorders can cause short- and long-term impairment in daily activities. Objective: To investigate the sleep of family caregivers of elderly people with Parkinson's and/or Alzheimer's disease. Method: Exploratory and descriptive research with a quantitative approach, whose target audience will be family caregivers of elderly people with Parkinson's and/or Alzheimer's disease, assisted by the Reviver research and extension project of the Federal University of Amapá. Expected results: It is expected to know about the quality of sleep of family caregivers of elderly people living with Parkinson's disease and/or Alzheimer's disease. These data will be able to constitute a base for future planning of health actions that aim to make possible the well-being and general health of the family caregivers through the reduction of aggravations caused by interferences in the sleep cycle.
Keywords: Saúde do idoso; Sobrecarga do cuidador; Saúde do idoso; Sobrecarga do cuidador; CNPQ::CIENCIAS DA SAUDE::ENFERMAGEM; ODS 3 – Saúde e bem-estar; ODS 10 – Redução das desigualdades